THE ROLE OF MACEDONIAN COMPOSER AND ETNHNOMUSICOLOGIST ŽIVKO FIRFOV IN CONTEMPORARY MACEDONIAN MUSIC CULTURE (Philological Studies, 2020)
This paper presents the life and activities of Živko Firfov, who is observed as one of the important artists of Contemporary Music Culture in the History of Macedonian music. Firfov is significant in Macedonian music because he has made a great contribution to discovering, writing, acquainting and affirming Macedonian folk music both domestically and abroad.
Keywords: composer; ethnomusicologist; Macedonian folk music; Contemporary Music Culture